2017
DOI: 10.1039/c7cc05706g
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(ii) complexes of pyridinol and N-heterocyclic carbene derived pincers as robust catalysts for selective carbon dioxide reduction

Abstract: New methoxy substituted CNC pincers form ruthenium catalysts that are robust and convert CO2 to CO selectively using light energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 40 publications
3
69
0
Order By: Relevance
“…For pincer carbene chemistry, Ru is one of the most studied metal centers. In this regard, Papish's group presented a few examples of octahedral Ru II complexes ( 19 and 20 , Scheme 9), and tested their performance in photocatalytic reduction of CO 2 [19] . Similar to the case shown in Scheme 1, the group again found that the catalytic property can be largely affected by the remote substituent.…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 89%
“…For pincer carbene chemistry, Ru is one of the most studied metal centers. In this regard, Papish's group presented a few examples of octahedral Ru II complexes ( 19 and 20 , Scheme 9), and tested their performance in photocatalytic reduction of CO 2 [19] . Similar to the case shown in Scheme 1, the group again found that the catalytic property can be largely affected by the remote substituent.…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 89%
“…The study of ruthenium‐based molecular catalysts driving the CRR reaction remains an intense and attractive area of research . Recent studies on the photocatalytic CRR with [Ru II (bpy) 2 (CO) 2 ][PF 6 ] 2 ( Ru‐1 ) and a pyridinol‐derived pincer ligated ruthenium chloride complex ( Ru‐2 ) have revealed higher rates of reactivity and a higher durability of the pincer complex . Additionally, electrocatalysis appeared to be faster with Ru‐2 and halide‐free Ru‐3 (vs. Ru‐1 ) via preliminary cyclic voltammetry (CV) analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the photocatalytic CRR with [Ru II (bpy) 2 (CO) 2 ][PF 6 ] 2 ( Ru‐1 ) and a pyridinol‐derived pincer ligated ruthenium chloride complex ( Ru‐2 ) have revealed higher rates of reactivity and a higher durability of the pincer complex . Additionally, electrocatalysis appeared to be faster with Ru‐2 and halide‐free Ru‐3 (vs. Ru‐1 ) via preliminary cyclic voltammetry (CV) analysis . Access to the active catalyst via ligand dissociation is an important step for coordinatively saturated metal centers.…”
Section: Introductionmentioning
confidence: 99%
“…A similar CNC ruthenium complex, [(CNC OMe )RuCl(NCMe) 2 ]OTf, in which a 4‐methoxy group is introduced to the pyridyl moiety in CNC ligand, has been reported . The use of this complex for the photocatalytic CO 2 reduction in CH 3 CN with photosensitizer [Ir(ppy) 3 ] resulted in selective production of CO (TON CO =227; selectivity 97 %), but in DMF with photosensitizer [Ru(bpy) 3 ] 2+ production of formate was dominant (TON HCOOH =143; selectivity 90 %).…”
Section: Figurementioning
confidence: 99%